Tetraaqua(1,10-phenanthroline-κ(2) N,N′)magnesium(II) bis[(2,4-dichlorophenyl)acetate] - Hao, Xiao-Min (International Union of Crystallography, 2008)
In the mononuclear title complex, [Mg(C(12)H(8)N(2))(H(2)O)(4)](C(8)H(5)Cl(2)O(2))(2), each Mg(II) ion is hexacoordinated by two N atoms from a 1,10-phenanthroline ligand [Mg—N = 2.233 (2) Å] and four water molecules [Mg—OW = 2.033 (2) and 2.043 (1) Å] in a distorted octahedral geometry. A twofold rotation axis passes through the Mg atom. In the crystal structure, the cations and anions are linked by intermolecular O—H⋯O hydrogen bonds and π–π stacking interactions [centroid–centroid distance = 3.804 (2) Å] into layers parallel to the ac plane.